Faithful simulation and detection of quantum spin Hall effect on superconducting circuits. Issue 1 (26th January 2021) - Liu, Jia; Cao, Jun‐Yi; Chen, Gang; Xue, Zheng‐Yuan
Abstract: Topological states of quantum matter have inspired both fascinating physics findings and exciting opportunities for applications. Due to the overcomplicated structure of, as well as interactions between, real materials, a faithful quantum simulation of topological matter is very important in deepening our understanding of these states. This requirement puts the quantum superconducting circuits system as a good option for mimicking topological materials, owing to their flexible tunability and fine controllability. As a typical example herein, we realize a ℤ 2 ‐type topological insulator featuring the quantum spin Hall effect state, using a coupled system of transmission‐line resonators and transmons. The single‐excitation eigenstates of each unit cell are used as a pseudo‐spin 1/2 system. The boundary of the topological phase transition is fixed in the phase diagram. Topological edge states are shown, which can be experimentally verified by detecting the population at the boundary of the plane. Compared with the previous simulations, this compositional system is fairly controllable, stable, and less limited. Therefore, our scheme provides a reliable platform for faithful quantum simulations of topological matter.